Challenges and opportunities in applying scientific approach: The case of mathematics learning - Murni, Murni; Asmawati, Asmawati; Aryani, Irma; Abdussakir, Abdussakir; Rofiki, Imam (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2020)
A scientific approach provides opportunities for students to organize student learning experiences in a logical order. Some previous studies results indicated that mathematics teaching strategies using a scientific approach could improve students’ learning achievement. However, teachers still experience difficulties in implementing mathematics learning. Therefore, this study wants to uncover teachers’ obstacles in implementing mathematics learning with a scientific approach. This explorative study involved 19 mathematics teachers in Aceh Besar, Indonesia. The study approach used is qualitative. Data were collected through observations, interviews, and field notes. The results showed that the dominance of teacher obstacles was a mastery factor in the concept of a scientific approach and classroom management. Some teachers also have difficulties in designing and implementing mathematics learning with a scientific approach. The teacher still feels confused about applying all the five steps of the scientific approach.